Investigating the impacts of auditory and visual feedback in advanced driver assistance systems: a pilot study on driver behavior and emotional response - Zou, Zhao; Khan, Aila; Lwin, Michael; Alnajjar, Fady; Mubin, Omar (Frontiers in Computer Science, 2025)
In the autonomous vehicle industry, Advanced Driver Assistance Systems (ADAS) are recognized for their capacity to enhance service quality, improve on-road safety, and increase driver comfort. Driver Assistance Systems are able to provide multi-modal feedback including auditory cues, visual cues, vibrotactile cues and so on. The study will concentrate on assessing the impacts of auditory and visual feedback from assistive driving systems on drivers. A group consisting of five participants (N = 5) was recruited to take part in two sets of driving experiments. During the experimental sessions, they were exposed to several reminders designed for drivers in audio-only format and audio-visual format, respectively. Their driving behaviors and performances were under researcher’s observation, while their emotions were evaluated by YOLO v5 detecting model. The results reveal that the participants higher compliance rate and strong emotional reactions (especially the feelings of anger, sadness and surprise) towards the unimodal feedback of audio-only driving reminders. There is no strong evidence showing that the bimodal ADAS feedback of audio-visual cues effectively improve drivers’ performance during driving period. However, both the emotion data and user satisfaction results indicate that participants experienced an increase in feelings of happiness when they were able to visualize the AI assistant while hearing the audio reminders from the assistant. The study serves as one of the pioneering studies aimed at enhancing the theoretical foundation in the field of automotive user interface design, particularly concerning the design of auditory functions.